Strategi Meningkatkan Efektifitas Pengelolaan Pendapatan Asli Daerah di Provinsi Riau - Syapsan Syapsan (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The role of the regional government in Indonesia has become a central role. Since the regional autonomy was implemented, the regional government has a mandate to prosper the community even the Regional Original Revenue (PAD) was run uncertainly in day by day. Therefore, it is necessary to make a strategic step on how to manage the local own revenue effectively. The result of descriptive research methods, that Riau Province performance study in achieving Local Original Revenue (PAD) target by three regions studied, mostly decreased with below than 100% of effectiveness value percentage, means it is not effective. So that, there is overestimated while determine the achievable target. Strategic steps need to be taken as an effort to improve it through a data collection strategy for taxpayers, in the context of increasing regional tax revenue; Strategies for cooperation with the private sector / NGOs in the management and collection of regional taxes; Strategies to improve local tax management; Strategy to expand regional tax bases; Strategies to re-identifying the mission and mandate of the organization; The strategy of holding computerized regional revenue.